Konsep Kelahiran Baru Dalam Pembelajaran Pendidikan Agama Kristen - Oci, Markus (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2020)
Abstract. Christian Education as an educational process that is an essential effort by teachers or educators aimed at students in the learning process. The education contains teachings, Christian values, and emphasis on the three aspects, namely: cognitive (knowledge), affective (attitude), psychomotor (skills and skills), which in the process of teaching and learning activities knowledge about the Bible including dogmas that are based on the truth of God's Word (Biblical). The subjects of Christian Religious Education are churches and schools. The Object of Christian Religious Education is teaching and learning activities consisting of believers of all ages (from children to the elderly). This research uses the literature method. The New Birth is born again by God for every believer in the Lord Jesus Christ. As an implication of Christian Religious Education, one of them is about "New Birth," meaning that students must experience a personal encounter with the Lord Jesus Christ called the New Birth.Abstrak. Pendidikan Agama Kristen sebagai proses pendidikan yang merupakan usaha sadar oleh pengajar atau pendidik yang ditujukan kepada anak didik dalam proses pembelajarannya yang berisikan ajaran-ajaran, nilai-nilai kekristenan serta penekanannya kepada ketiga aspek pendidikan yaitu: kognitif (pengetahuan), afektif (sikap), psikomotor (skill dan keterampilan), dimana dalam proses kegiatan belajar mengajar pengetahuan tentang Alkitab termasuk dogma-dogma yang berdasarkan pada kebenaran Firman Tuhan (Alkitabiah). Subyek Pendidikan Agama Kristen adalah gereja dan sekolah. Obyek Pendidikan Agama Kristen adalah kegiatan belajar  mengajar terdiri dari orang-orang percaya dari segala usia (dari anak-anak sampai pada lansia). Penelitian ini menggunakan metode literatur. Sebagai implikasi dari Pendidikan Agama Kristen salah satunya tentang “Kelahiran baru” artinya peserta didik harus mengalami perjumpaan secara pribadi dengan Tuhan Yesus Kristus yang disebut dengan Kelahiran Baru.